Respuesta :
Substitute for x in the second equation:-
2(y + 3) + y = 9
2y + 6 + y = 9
3y = 9 - 6 = 3
so y = 3/3 = 1
Now plug this value of y into first eqution:-
x = 1 + 3 = 4
So you answer is x = 4 and y = 1.
2(y + 3) + y = 9
2y + 6 + y = 9
3y = 9 - 6 = 3
so y = 3/3 = 1
Now plug this value of y into first eqution:-
x = 1 + 3 = 4
So you answer is x = 4 and y = 1.
Answer:
Substitute for x in the second equation:-
2(y + 3) + y = 9
2y + 6 + y = 9
3y = 9 - 6 = 3
so y = 3/3 = 1
Now plug this value of y into first eqution:-
x = 1 + 3 = 4
So you answer is x = 4 and y = 1.
Step-by-step explanation: